2006
DOI: 10.1590/s0044-59672006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Tambaqui growth and survival when exposed to different photoperiods

Abstract: The use of different photoperiods (light) were investigated during tambaqui (Colossoma macropomum) juvenile growth under captivity. Light intensity tested was: continuous dark (24hrs without light), natural photoperiod simulation (10hrs of light and 14hrs without light) and continuous light (24 with light). No mortality was recorded among treatments. Significant differences was observed after 50 days of experiment among mean fish weight, fish kept under a continuous darkness showed a better specific growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In the treatments where it was applied the natural photoperiod found by tambaqui in nature, the feed efficiency was compromised, as previously described by Aride et al (2006). Thus, in our study, the best feed conversion for the D-32 group may be associated with the fact that the animal is prepared to process the food near or at night.…”
Section: Timesupporting
confidence: 68%
“…In the treatments where it was applied the natural photoperiod found by tambaqui in nature, the feed efficiency was compromised, as previously described by Aride et al (2006). Thus, in our study, the best feed conversion for the D-32 group may be associated with the fact that the animal is prepared to process the food near or at night.…”
Section: Timesupporting
confidence: 68%
“…There was no significant difference among the experimental units and averages complied with the recommended range for the production of tropical fish, such as the tambaqui (BOYD, 1992;SIPAÚBA-TAVARES, 1995;ARIDE et al, 2006;RADÜNZ NETO, 2010).…”
Section: Resultsmentioning
confidence: 74%
“…These results differ from those observed for Sparus aurata fed different levels of vitamin C (25, 50, 100 and 200 mg/kg) (Henrique et al, 1998) and tambaqui fed 200 and 400 mg ascorbic acid/kg feed and exposed to hypoxia (Chagas and Val, 2006), where the evaluated specimens showed no differences in plasma glucose values during the feeding period. Aride et al, (2006) also found no significant differences in tambaqui specimens subjected to different photoperiods. According to Pickering and Pottinger (1995) and Reid et al, (1998), various species of fish exhibit primary responses to stress, such as increased circulating catecholamines and corticosteroids, thus triggering secondary effects related to energy requirements, such as increased blood glucose by glycogenolysis and gluconeogenesis.…”
Section: Resultsmentioning
confidence: 75%